Permeable Concrete-based on Construction and Demolition waste Aggregates used in Permeable Paving Slabs - Elaine Vazquez; Almir Vidal; Mohammad K Najjar; Assed Haddad; Mayara Amario (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
The recycling of construction and demolition waste is one of the solutions for reducing the environmental impacts, where residues can be used in permeable paving, produced with large recycled aggregates. The novelty herein is to conduct an experimental testing stage for producing permeable concrete slabs, using coarse Recycled aggregates from Construction and Demolition waste, as a future application in permeable paving. The methodology consists of evaluating the effects of Construction and Demolition waste aggregates on the properties of permeable concrete in the fresh state and the hardened state. Permeable concrete slabs were produced based on five types of concrete mixtures, which can be applied as a final coating on soils with permeable profiles. A sustainable environment contributes to the improvement of knowledge and development on one of the applications of permeable concrete elements by recycling the waste generated by Civil Construction activities, mainly from non-renewable resources.